NUMERACY LITERACY IN ELEMENTARY EDUCATION: A LITERATURE-BASED ANALYSIS OF STRATEGIES TO ENHANCE STUDENTS' FOUNDATIONAL COMPETENCIES - Juita Sari (CV. Fahr Publishing, 2025)
This study aims to explore and synthesize various strategies used to enhance numeracy literacy in elementary education, focusing on strengthening students’ foundational competencies. Recognizing the increasing demand for integrated skills in 21st-century education, the research adopts a literature-based method by reviewing empirical studies and theoretical papers from the last five years. The literature was gathered from reputable databases such as Scopus, DOAJ, and Google Scholar, using specific inclusion criteria that emphasize elementary-level interventions combining numeracy and literacy skills. The analysis reveals five dominant strategy categories: digital media integration, Realistic Mathematics Education (RME), project-based learning, textual problem-solving, and cross-curricular integration. These approaches were found to improve student engagement, comprehension, and problem-solving abilities; however, their success is highly dependent on contextual factors like teacher readiness, infrastructure availability, and student reading proficiency. The novelty of this research lies in its conceptual framing of numeracy literacy as an integrated skillset, as well as in its development of a strategic taxonomy tailored for primary-level education, which has not been extensively addressed in previous literature. Moreover, the study identifies implementation gaps and proposes a comprehensive framework that links strategy types with enabling conditions. In conclusion, this research provides actionable insights for educators, policymakers, and curriculum developers by mapping effective, scalable approaches to integrate literacy and numeracy in elementary learning environments. The findings contribute both theoretically and practically to the global discourse on improving foundational learning outcomes.